Factors associated with changes in creatine phosphokinase (CPK) in trauma patients submitted to the “Red Wave”, with evolution to rhabdomyolysis - PASTORE NETO,MARIO (2018)
ABSTRACT Objective: to identify and analyze factors associated with plasma creatine phosphokinase (CPK) levels in trauma victims with progression to rhabdomyolysis. Methods: we conducted a prospective, longitudinal study, with 50 patients submitted to the “Red Wave” protocol, with evolution to rhabdomyolysis after hospital admission. We studied the variables age, gender, trauma scores, mechanism and outcome, CPK at admission and final, intervals of days between laboratory evaluations, surgery and complications. We stratified CPK values in <500U/L, ≥500 - <1000 U/L, and ≥1000U/L, with calculation of the difference between the initial and final values. Results: at admission, 83% of patients (n=39) had CPK≥1000U/L, with predominance of blunt trauma and thoracic injury (p<0.05), as well as orthopedic fracture, acute renal failure and gastrointestinal bleeding, CPK being lower in those without acute renal injury, with a trend towards statistical significance. There were no differences in final CPK stratification. Factors that were independently associated with the greater CPK variation were, positively, hospitalization time greater than one week and compartment syndrome, and negatively, acute renal injury. Conclusion: the CPK level of 1000U/L remains the lower limit, with importance for early intervention in worsening conditions such as digestive hemorrhage, acute renal injury and compartment syndrome, which implied greater absolute differences between initial and final CPK, in addition to blunt trauma, thoracic injury and orthopedic fracture.